Clopidogrel versus aspirin monotherapy following dual antiplatelet therapy after percutaneous coronary intervention: an updated meta-analysis of 162,829 patients - Mohammed A. Elbahloul; Ahmed Mansour; Amr Galal; Walaa M. Moawad; Manar Khaled; Ahmed Wahdan Kasem; Eman E. Labeeb; Islam Y. Elgendy (European Journal of Clinical Pharmacology, 2026)
Background Dual antiplatelet therapy (DAPT) following percutaneous coronary intervention (PCI) remains a cornerstone for preventing ischemic events; however, the optimal long-term single antiplatelet therapy after completion of DAPT remains unclear. We aimed to compare clopidogrel and aspirin monotherapy after completion of the standard duration of DAPT. Methods A systematic search was conducted on PubMed, Scopus, Cochrane Library, and Web of Science from inception to April 2025. We included randomized clinical trials and observational studies that compared aspirin versus clopidogrel monotherapy after completion of standard-duration DAPT. The primary and co-primary outcomes were major adverse cardiovascular events (MACE) and major bleeding, respectively. Using random-effects models, outcomes were expressed as risk ratios (RR) or hazard ratios (HR) with 95% confidence intervals (CI). Results Ten studies, comprising 162,829 patients, were included. Clopidogrel was significantly associated with a lower risk of MACE (HR: 0.72, 95% CI: 0.66–0.79) and net adverse clinical events (NACE) (RR: 0.86, 95% CI: 0.73–0.99) at a weighted mean follow-up of 3.2 years. Major bleeding showed no significant difference between clopidogrel and aspirin (RR: 0.85, 95% CI: 0.60–1.21). Moreover, there was no difference between clopidogrel and aspirin in all-cause mortality, myocardial infarction, revascularization, stroke, or all bleeding. Conclusion Among patients who underwent PCI, clopidogrel monotherapy after standard DAPT was associated with a lower incidence of MACE and NACE compared with aspirin monotherapy, without increasing the bleeding risk.